Quotient of Ideals of an Intuitionistic Fuzzy Lattice - K. V. Thomas; Latha S. Nair (Advances in Fuzzy Systems)
The concept of intuitionistic fuzzy ideal of an intuitionistic fuzzy lattice is introduced, and its certain characterizations are provided. We defined the quotient (or residual) of ideals of an intuitionistic fuzzy sublattice and studied their properties.